Sexting, Online Sexual Victimization, and Psychopathology Correlates by Sex: Depression, Anxiety, and Global Psychopathology - Gasso, Aina M.; Mueller-Johnson, Katrin; Montiel, Irene (International Journal of Environmental Research and Public Health, 2020)
Recent research on sexting highlighted a relationship between this new technology-mediated behavior and psychopathology correlates, although up to date results are mixed, and so far, studies have often used simple and not clinically validated measures of mental health. This study aimed to investigate sexting behaviors, online sexual victimization, and related mental health correlates using clinically validated measures for global psychopathology, anxiety, and depression; and doing so separately for men and women. The sample consisted of 1370 Spanish college students (73.6% female; 21.4 mean age; SD = 4.85) who took part in an online survey about their engagement in sexting behaviors, online sexual victimization behaviors, and psychopathological symptomatology, measured by a sexting scale and the Listado de Sintomas Breve (brief symptom checklist) (LSB-50), respectively. Out of our total sample, 37.1% of participants had created and sent their own sexual content (active sexting), 60.3% had received sexual content (passive sexting), and 35.5% had both sent and received sexual content, with significant differences between male and female engagement in passive sexting. No differences were found between men and women in the prevalence of their victimization by nonconsensual dissemination of sexual content; however, women were more pressured and threatened into sexting than men. Sex differences in psychopathology were found only for depression prevalence rates but not for global psychopathology or anxiety. Furthermore, for male participants, our results showed a significant association only between online sexual victimization and psychopathology but not for consensual active and passive sexting. However, for the female participants, active sexting, passive sexting, and online sexual victimization were all associated with poorer mental health. Implications for prevention and intervention are discussed.
Keywords: sexting; mental health; psychopathology; victimization; sex; JCR; Scopus